Strategies for the improvement of social skills in students with autism spectrum disorder: Intensive support for inclusive education - Fortuny-Guasch, Rosa; Sanahuja-Gavaldà, Jose Maria; Pérez-Romero, Antonio (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Students with Autism Spectrum Disorder (ASD) typically have impaired social skills, which makes it difficult for them to become independent adults. For this reason, it is essential that the development of social skills is one of the main objectives within inclusive schools, allowing children with ASD to benefit from both education and interaction with their peers without ASD. Objective. Therefore, the aim of the study is to analyze the strategies used in inclusive contexts to promote the development of social skills in students with as ASD. Method. Twenty students with ASD aged 6-11 years participated in the study. Direct observation and conducting interviews with their respective teachers allowed us to analyze teaching strategies that improved the social skills of students with ASD within the mainstream school. Results. The results show that social interaction is initiated mostly by teachers and peers, and when a child with ASD starts, it is preferably directed toward a support teacher. In addition, social interaction is strongly influenced by the activity developed in the classroom and by the role of the support teacher, who becomes a key player. Conclusion. We concluded that the development of social skills in students with ASD depends on the degree of structuring of the spaces and activities where students with ASD participate, the role of the teacher, and the typology of curricular activities.
Keywords: social skills; autism spectrum disorder (ASD); inclusive education; teaching strategies; support teacher